Surface ruptures and building damage of the 2003 Bam, Iran, earthquake mapped by satellite synthetic aperture radar interferometric correlation - Fielding, E; Talebian, M; Rosen, P; Nazari, H; Jackson, J; Ghorashi, M; Walker, R (2005)
We use the interferometric correlation from Envisat synthetic aperture radar (SAR) images to map the details of the surface ruptures related to the 26 December 2003 earthquake that devastated Bam, Iran. The main strike-slip fault rupture south of the city of Bam has a series of four segments with left steps shown by a narrow line of low correlation in the coseismic interferogram. This also has a clear expression in the field because of the net extension across the fault. Just south of the city limits, the surface strain becomes distributed over a width of about 500 m, probably because of a thicker layer of soft sedimentary material. Another fault north of Bam shows offset and low correlation over a wider zone in the interferograms, but it has no discrete surface rupture, possibly because of a net shortening across this fault. Taking the difference between the interferometric correlation for an interval including the earthquake and an interval before the earthquake separates the changes due to the earthquake from other effects in the partially vegetated city of Bam. We map the damage to buildings by measuring the change from high correlation to low correlation where buildings were destroyed by the earthquake. Copyright 2005 by the American Geophysical Union.